2002
DOI: 10.2166/ws.2002.0021
|View full text |Cite
|
Sign up to set email alerts
|

Spores of sulphite-reducing clostridia (SSRC) as surrogate for verification of the inactivation capacity of full-scale ozonation for Cryptosporidium

Abstract: The inactivation of C. parvum and spores of Cl. perfringens by ozone treatment in natural water in a lab-scale continuous-flow system was compared. In addition the inactivation of the natural occurring spores of sulphite-reducing clostridia (SSRC) in this water was monitored in one of the lab-scale systems as well as in a full-scale ozonation process. The survival ratio of C. parvum oocysts was determined using the CD-1 neonatal mouse infectivity test and for Cl. perfringens and SSRC the survival ratio was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…This was concluded from the results of lab-scale study with C. perfringens and SSRC monitoring under full-scale conditions (Hijnen et al, 2000a). The susceptibility of the lab-cultured C. perfringens, C. parvum (animal infectivity; Hijnen et al (2002)), and environmental SSRC (Hijnen et al (2000a) and this study) for ozone are in the same order of magnitude. Driedger et al (2001) concluded that B. subtilis is a good surrogate for C. parvum at high temperatures, but is more readily inactivated at low temperatures.…”
Section: Assessment Of Full-scale Disinfection Capacitysupporting
confidence: 53%
See 4 more Smart Citations
“…This was concluded from the results of lab-scale study with C. perfringens and SSRC monitoring under full-scale conditions (Hijnen et al, 2000a). The susceptibility of the lab-cultured C. perfringens, C. parvum (animal infectivity; Hijnen et al (2002)), and environmental SSRC (Hijnen et al (2000a) and this study) for ozone are in the same order of magnitude. Driedger et al (2001) concluded that B. subtilis is a good surrogate for C. parvum at high temperatures, but is more readily inactivated at low temperatures.…”
Section: Assessment Of Full-scale Disinfection Capacitysupporting
confidence: 53%
“…As described before (Hijnen et al, 2002) and presented in Figure 2, the disinfection kinetics of C. perfringens spores in the WBE water can be described by the Chick model with an inactivation rate constant k of −0.25 (SD = 0.014; p<0.001; n=1).…”
Section: Inactivation Kineticsmentioning
confidence: 76%
See 3 more Smart Citations